MEMPELAJARI PENGARUH KONSENTRASI EKSTRAK RIMPANG LENGKUAS (Alpinia galanga) TERHADAP PERTUMBUHAN Aspergillus flavus PADA KACANG TANAH - Made Dharma Puthera, Anak Agung; Ngurah Agung, I Gusti; Selamet Duniaji, Agus (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 2 No 1 (2013): Jurnal ITEPA, 2013)
This study conducted to determine the optimal concentration of galangal rhizome extract (Alpinia galanga) for inhibiting the growth of A. flavus in peanuts. The concentration of Alpinia galanga extract used in this study were 0.1%, 0.2%, 0.3%, and 0.4%. In this study using a descriptive analysis and displaying the results of the research presented in images and tables. While quantitative data were also analyzed by the method of completely randomized design (CRD) analyzed by analysis of variance and continued with different test by Least Significant Difference test (LSD 5%). The results showed that the crude extract of (Alpinia galanga) had the ability to inhibit the growth of A. flavus, with very strong categorized on PDA. At a concentration of 0.4% did not find any growth of A. flavus, whereas the largest population grows at a concentration of Alpinia galanga ekstract 0.0% (without the exstract Alpinia galanga) that was 121.33 x 103 cfu / g. At a concentration of 0.4% was also able to inhibit the growth of A. flavus that contaminate peanuts with the inhibition of up to 100%.
Keywords: Ginger rhizome, Aspergillus flavus, Peanut.